Seminal biomarkers for the evaluation of male infertility - Jared M Bieniek; Andrei P Drabovich; Kirk C Lo (Asian Journal of Andrology, 2016)
For men struggling to conceive with their partners, diagnostic tools are limited and often consist of only a standard semen analysis. This baseline test serves as a crude estimation of male fertility, leaving patients and clinicians in need of additional diagnostic biomarkers. Seminal fluid contains the highest concentration of molecules from the male reproductive glands, therefore, this review focuses on current and novel seminal biomarkers in certain male infertility scenarios, including natural fertility, differentiating azoospermia etiologies, and predicting assisted reproductive technique success. Currently available tests include antisperm antibody assays, DNA fragmentation index, sperm fluorescence in situ hybridization, and other historical sperm functional tests. The poor diagnostic ability of current assays has led to continued efforts to find more predictive biomarkers. Emerging research in the fields of genomics, epigenetics, proteomics, transcriptomics, and metabolomics holds promise for the development of novel male infertility biomarkers. Seminal protein-based assays of TEX101, ECM1, and ACRV1 are already available or under final development for clinical use. Additional panels of DNA, RNA, proteins, or metabolites are being explored as we attempt to understand the pathophysiologic processes of male infertility. Future ventures will need to continue data integration and validation for the development of clinically useful infertility biomarkers to aid in male infertility diagnosis, treatment, and counseling.